Is There News in Inventories? - Christoph Görtz; Christopher Gunn; Thomas A. Lubik (Center for Economic Studies and ifo Institute (CESifo), 2020)
We identify total factor productivity (TFP) news shocks using standard VAR methodology and document a new stylized fact: in response to news about future increases in TFP, inventories rise and comove positively with other major macroeconomic aggregates. We show that the standard theoretical model used to capture the effects of news shocks cannot replicate this fact when extended to include inventories. To explain the empirical inventory behavior, we therefore develop a framework that relies on the presence of knowledge capital accumulated through a learning-by-doing process. The desire to take advantage of higher future TFP through knowledge capital drives output and hours choices on the arrival of news and leads to inventory accumulation alongside the other macroeconomic variables. The broad-based comovement we document supports the view that news shocks are an important driver of aggregate fluctuations.
Keywords: E20; E30; 330; news shocks; business cycles; inventories; knowledge capital; VAR